A Rare Case of Duodenal Adenocarcinoma Presenting as a Subepithelial Lesion in a Patient Undergoing Investigation for Iron Deficiency Anaemia - Xinxin Hu; Karina Aivazian; Catriona McKenzie; May Wong; Arthur Kaffes; Payal Saxena (Case Reports in Gastrointestinal Medicine)
Introduction. Adenocarcinomas account for approximately 40% of small bowel cancers. They are typically mucosal lesions with distinctive features on endoscopy. We describe a rare case of duodenal adenocarcinoma presenting as a subepithelial lesion which posed a diagnostic challenge. Case. An 85-year-old male patient presented for investigation of iron deficiency anaemia. Initial upper endoscopy found a subepithelial duodenal lesion with central depression but otherwise normal appearing mucosa. Superficial biopsies of the duodenal lesion were unremarkable. Subsequent antegrade single balloon enteroscopy revealed active bleeding from the lesion which was refractory to endoscopic treatment. A complete local excision of the lesion via laparotomy was necessary to achieve haemostasis. Histopathology from the lesion showed a moderately differentiated duodenal adenocarcinoma with invasion into the submucosa but no evidence of lymphovascular spread. Conclusion. Duodenal adenocarcinomas are rare gastrointestinal tumours associated with a poor prognosis. This case report outlines a rare presentation of duodenal adenocarcinoma and highlights the importance of judicious assessment of lesions found on endoscopy. Advances in endoscopic diagnostic modalities could facilitate early diagnosis and improve therapeutic outcomes.